Last sons of America - Johnson, Phillip Kennedy (BOOM! Studios, a division of Boom Entertainment, Inc., 2017)
"Originally published in single magazine form as Last Sons of America No. 1-4."--Indicia
Keywords: Entführung; Sterilität; Biologische Waffe; Adoption; Terrorismus; Amerika; Brothers / Comic books, strips, etc; Intercountry adoption / Comic books, strips, etc; Infertility / Comic books, strips, etc; Kidnapping / Comic books, strips, etc; Child trafficking / Nicaragua / Comic books, strips, etc; Drug traffic / Nicaragua / Comic books, strips, etc; Brothers; Child trafficking; Drug traffic; Infertility; Intercountry adoption; Kidnapping; Nicaragua; Comics (Graphic works); Graphic novels; Noir comics; Comic